2021
DOI: 10.1111/ijcp.14881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimodal preemptive analgesia on postoperative gastrointestinal function and clinical outcome in patients undergoing laparoscopic colorectal surgery

Abstract: Objective This study aimed to investigate the effects of multimodal preemptive analgesia on postoperative gastrointestinal function and clinical outcomes in patients undergoing laparoscopic colorectal surgery. Methods This prospective study included a total of 108 patients undergoing elective laparoscopic colorectal surgery from June 2019 to June 2020. The patients were divided into the control group and the study group according to the random number table method. Patients in the study group were given flurbip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our data showed that TAPB and RSB, when performed preoperatively, can reduce the levels of IL-6 and hs-CRP, which is basically consistent with the results of previous studies [ 22 , 44 ]. Preemptive analgesia has been reported to reduce the inflammatory response caused by surgery [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that TAPB and RSB, when performed preoperatively, can reduce the levels of IL-6 and hs-CRP, which is basically consistent with the results of previous studies [ 22 , 44 ]. Preemptive analgesia has been reported to reduce the inflammatory response caused by surgery [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…And intraoperative anesthesia is to ensure that the procedure would be able to give patients the basic conditions in order to alleviate patients' postoperative pain and intraoperative pain with strong stress response, to make patients achieve ideal anesthesia in the operation, and effective anesthesia can help patients with postoperative recovery and reduce the postoperative complications of [ 4 , 5 ]. As one of the effective analgesic methods of anesthesia combined with multimode analgesia technology, TAPB block has achieved good analgesic effect in minimally invasive laparoscopic surgery, which can effectively relieve patients' body pain, but its deficiency is that it cannot be used as visceral analgesia [ 6 , 7 ]. As one of the effective methods of postoperative multimode analgesia technology, ultrasound guided QLB block can improve the deficiency of TAPB and effectively relieve patients' visceral pain, which is widely used in gastrointestinal surgery, gynecological surgery, and other surgeries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of postoperative complications was 19.4%. 7 , 8 , 11–14 Therefore, in this study, we sought to summarize the best evidence for accelerating the postoperative recovery of gastrointestinal function in patients with CRC to offer a scientific, standardized, and reliable evidence basis for clinical practice.…”
Section: Introductionmentioning
confidence: 99%